Anxiolytic- and antidepressant-like effects of the methadone metabolite 2-ethyl-5-methyl-3, 3-diphenyl-1-pyrroline (EMDP). (February 2016) - Forcelli, Patrick A.; Turner, Jill R.; Lee, Bridgin G.; Olson, Thao T.; Xie, Teresa; Xiao, Yingxian; Blendy, Julie A.; Kellar, Kenneth J.
Abstract: The enhancement of GABAergic and monoaminergic neurotransmission has been the mainstay of pharmacotherapy and the focus of drug-discovery for anxiety and depressive disorders for several decades. However, the significant limitations of drugs used for these disorders underscores the need for novel therapeutic targets. Neuronal nicotinic acetylcholine receptors (nAChRs) may represent one such target. For example, mecamylamine, a non-competitive antagonist of nAChRs, displays positive effects in preclinical tests for anxiolytic and antidepressant activity in rodents. In addition, nicotine elicits similar effects in rodent models, possibly by receptor desensitization. Previous studies (Xiao et al., 2001) have identified two metabolites of methadone, EMDP (2-ethyl-5-methyl-3, 3-diphenyl-1-pyrroline) and EDDP (2-ethylidene-1, 5-dimethyl-3, 3-diphenylpyrrolidine), which are considered to be inactive at opiate receptors, as relatively potent noncompetitive channel blockers of rat α3β4 nAChRs. Here, we show that these compounds are likewise highly effective blockers of human α3β4 and α4β2 nAChRs. Moreover, we show that they display relatively low affinity for opiate binding sites labeled by [ 3 H]-naloxone. We then evaluated these compounds in rats and mice in preclinical behavioral models predictive of potential anxiolytic and antidepressant efficacy. We found that EMDP, but not EDDP, displayed robust effects predictive of anxiolytic and antidepressant efficacy without significant effects on locomotor activity. Moreover, EMDP at behaviorally active doses, unlike mecamylamine, did not produce eyelid ptosis, suggesting it may produce fewer autonomic side effects than mecamylamine. Thus, the methadone metabolite EMDP may represent a novel therapeutic avenue for the treatment of some affective disorders. Highlights: EMDP and EDDP block α3β4 and α4β2 nicotinic receptors. EMDP and EDDP displayed anxiolytic-like effects in the marble burying tests. EMDP displayed anxiolytic-like effects in the elevated plus maze. EMDP displayed antidepressant-like effects in mouse and rat forced swim tests. EMDP, unlike mecamylamine, did not cause eyelid ptosis.